Deciding to leave : the politics of retirement from the United States Supreme Court - Ward, Artemus, 1971- (Albany : State University of New York Press, 2003)
While much has been written on Supreme Court appointments, Deciding to Leave provides the first systematic look at the process by which justices decide to retire from the bench, and why this has become increasingly partisan in recent years. Since 1954, generous retirement provisions and decreasing workloads have allowed justices to depart strategically when a president of their own party occupies the White House. Otherwise, the justices remain in their seats, often past their ability to effectively participate in the work of the Court. While there are benefits and drawbacks to various reform proposals, Ward argues that mandatory retirement goes farthest in combating partisanship and protecting the institution of the Court.
Machine generated contents note: 1. Politics of Departure in the U.S. Supreme Court -- 2. 1789-1800: Traveling Postboys -- 3. 1801-1868: Crippled Courts -- 4. 1869-1896: Old Imbeciles on the Bench -- 5. 1897-1936: Old Fools and Young Spirits -- 6. 1937-1954: Senior Status -- 7. 1954-1970: The Limits of Power -- 8. 1971-1999: Appointed for Life -- 9. 2000-Present: A Self-Inflicted Wound -- 10. Conclusion: Imaginary Danger? -- App. A Letter from Byron White to Warren Burger, October 20 1975 -- App. B Letter from Warren E. Burger, William J. Brennan, Jr., Potter Stewart, Byron R. White, Thurgood Marshall, Harry A. Blackmun, Lewis F. Powell, and William H. Rehnquist to William O. Douglas, December 22, 1975 -- App. C Letter from John Paul Stevens to William H. Rehnquist, October 28, 1988.
Includes bibliographical references (pages 313-328) and index.
Print version record.
JSTOR
Keywords: United States. -- Supreme Court -- Officials and employees -- Retirement; États-Unis. -- Supreme Court -- Fonctionnaires -- Retraite; United States. -- Supreme Court; Judges -- Retirement -- United States; Juges -- Retraite -- États-Unis.; LAW -- Government -- Federal; Judges -- Retirement; Retirement; United States